Follow the drinking gourd - Winter, Jeanette (New York : Knopf, 1988)
By following the directions in a song, The drinking gourd, taught them by an old sailor named Peg Leg Joe, runaway slaves journey north along the Underground Railroad to freedom in Canada.
" A dragonfly book published by Alfred A. Knopf"
Keywords: Fugitive slaves -- Fiction; Slavery -- Fiction; Underground railroad -- Fiction